Comparative Analysis of Stock and Bond Performance in The Indonesian Capital Market - Putri Kemala Dewi Lubis; Limbong, Nikasyah; Sarah Lilya saragih; Sri Wulandari Tarigan; Iqbal Syahputra (ProBisnis : Jurnal Manajemen, 2024)
This research aims to analyze and compare the performance of shares and bonds in the Indonesian capital market during a certain period. This research will use qualitative methods and also a literature review. The aim is to gain knowledge about stock and bond trading on the Indonesian stock exchange, as well as carry out a comparative analysis between the two. Literary research is carried out by studying various sources such as books, journals, company annual reports, and websites to obtain information about financial theories and concepts, bonds, and capital markets. Apart from that, we also examine fundamental and external factors that influence stock prices, business operations and bonds on the Indonesian stock exchange. Our analysis shows that factors such as macroeconomic conditions, monetary policy, and market sentiment play an important role in determining company performance. In conclusion, this research provides valuable insights for investors and financial decision makers in understanding and exploiting investment opportunities in the Indonesian capital market. By understanding the differences and performance characteristics of stocks and bonds, investors can develop diverse and effective portfolio strategies to achieve long-term investment goals.